1991
DOI: 10.1128/mcb.11.3.1488
|View full text |Cite
|
Sign up to set email alerts
|

Chicken beta B1-crystallin gene expression: presence of conserved functional polyomavirus enhancer-like and octamer binding-like promoter elements found in non-lens genes.

Abstract: Expression of the chicken ,Bl-crystallin gene was examined. Northern (RNA) blot and primer extension analyses showed that while abundant in the lens, the OB1 mRNA is absent from the liver, brain, heart, skeletal muscle, and fibroblasts of the chicken embryo, suggesting lens specificity. Promoter fragments ranging from 434 to 126 bp of 5'-flanking sequence (plus 30 bp of exon 1) of the PB1 gene fused to the bacterial chloramphenicol acetyltransferase gene functioned much more efficiently in transfected embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…1A) (39). Site-directed mutagenesis of PL1 (M6A) and PL2 (M7) decrease chicken ␤B1-crystallin promoter activity (39).…”
mentioning
confidence: 99%
“…1A) (39). Site-directed mutagenesis of PL1 (M6A) and PL2 (M7) decrease chicken ␤B1-crystallin promoter activity (39).…”
mentioning
confidence: 99%
“…With regard to the ␤B1-crystallin gene, promoters of the mouse, chicken, and Xenopus have been investigated by in vitro or in vivo experiments (Roth et al, 1991;Duncan et al, 1995bDuncan et al, , 1996Chen et al, 2001;Cui et al, 2004;Mizuno et al, 2005). Likewise, results of those studies suggest that multiple regulators are implicated in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of potential regulatory elements comprising two Sp1 sites, two octamerbinding sequence-like sites (OL-1 and OL-2), and two polymavirus enhancer-like sites (PL-1 and PL-2, marked in Fig. 6A) were identified in the proximal region (Ϫ126/Ϫ53 bp) by in vitro analysis, showing that PL-1 seems to be a general activating element, whereas PL-2 is involved in lens specificity (Roth et al, 1991;Duncan et al, 1996). In vivo transgenic studies showed that the upstream regions of chicken (434 bp) and mouse (1,493 bp) ␤B1-crystallin are functional in the mouse (Duncan et al, 1995b(Duncan et al, , 1996Chen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations